"I Won't Buy This Product Again": The Boycott Determinants on Loyalty Using Animosity Model Approach - Dzikhrullah, Harits Dijani; Vania, Amelindha (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: The paper investigates the correlation between McDonald's consumption and protest actions in Indonesia, with a particular focus on customer loyalty, customer ethnocentrism, consumer efficacy, and war animosity.Methodology: This research used the animosity model technique and a sample of around 200 respondents, determined by purposive sampling methods. Data were analyzed using the PLS-SEM method with the help of SmartPLS 3.0 software.Finding: The research demonstrates that customer ethnocentrism, consumer efficacy, and war animosity have a positive impact on boycotts, however, boycotts have an important negative effect on loyalty.Conclusion: The research analyzes the viewpoints of McDonald's customers about the CEO's position on governmental interference in a foreign country, with a particular focus on the issue surrounding the company's product. Certain customers express their dissatisfaction, while others engage in a boycott of McDonald's to compel changes in company policies. The study is conducted in Aceh, a place renowned for its strong religious convictions, with a specific emphasis on the local responses to McDonald's conduct.